Expansion Mode Choices: The Case of US Multinationals in Brazil - Tourinho, Juliana Carvalho Sampaio; Sheng, Hsia Hua (Internext, 2017)
The traditional theory of expansion modes argue that local experience would bring Multinationals (MNEs) more knowledge of the particularities of the local market, mitigating subsequent same local expansion risk and will choose greenfield and wholly-owned subsidiary. However, local complementary inputs become relevant in this expansion decision, when local complementary assets are not always available and freely negotiated (Hennart, 2009). This paper analyzes the sequential expansion decision made by 10 major and large experienced US multinationals in Brazil between 2004 and 2013, identifying the possible motives for this decision considering MNEs expansion theories and Brazilian inter-regions differences. We found evidence that supports Hennart Bundling Model: i) the experience of multinationals in Brazil not always increases multinationals’ commitment in the host countries by establishment of new wholly-owned subsidiaries; ii) US MNEs make acquisitions when they need to enter in a new region with significant difference of local economic development from where MNE already operated; iii) also, Brazilian regional factors such as concentration, growth and industries’ intrinsic features are determinants of acquisitions and joint ventures choices